Paperboy - Vawter, Vince (New York : Delacorte Press, 2013)
When an eleven-year-old boy takes over a friend's newspaper route in July, 1959, in Memphis, his debilitating stutter makes for a memorable month.
Accelerated Reader AR
Keywords: Stuttering -- Juvenile fiction; Newspaper carriers -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Self-esteem -- Juvenile fiction; Race relations -- Juvenile fiction; Families -- Tennessee -- Juvenile fiction; Stuttering -- Fiction; Newspaper carriers -- Fiction; Interpersonal relations -- Fiction; Self-esteem -- Fiction; Race relations -- Fiction; Family life -- Tennessee -- Fiction; Memphis (Tenn.) -- History -- 20th century -- Juvenile fiction; Memphis (Tenn.) -- History -- 20th century -- Fiction